Pengaruh pemberian aditif cair buah naga merah (Hylocereus polyrhizus) terhadap kecernaan proein, energi metabolis dan produksi telur burung puyuh - Astuti, Rika Dwi; Wahyono, Fajar; Mangisah, Istna (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2015)
The study was aimed to evaluate the effect of liquid additive red dragon fruit as the addition of drinking water on the digestibility of protein, metabolizable energy and the production of quail eggs. Experimental animals used in the research were 200 female quails, 7 day old with average body weight of 13.61 ± 0.49 g. The experiment used a completely randomized design with 4 treatments and 5 replications : T0 (control), T1 (addition of a liquid additive red dragon fruit about 5 ml twice a day), T2 (once a day) and T3 (two days on time). The parameters measured were feed intake, digestibility of protein, metabolizable energy and production of quail eggs. Data were analyzed using a variety of F test at the level 5%, followed by Duncan’s Multiple Range test when there are significant effects on the treatment. The results showed that liquid additives red dragon fruit was not significant (P>0.05) on the digestibility of protein, metabolizable energy and the production of quail eggs. In conclusion, the adition of liquid additives reddragon fruit did not increase digestibility of protein, metabolizable energy and the production of quail eggs. Keywords: digestibility of crude protein, quail, quail egg production, red dragon fruit